Improving safety in anesthetized patients undergoing magnetic resonance imaging—Concept of time‐out in the MRI suite and measures to improve adherence to time‐out protocol. Issue 5 (16th January 2023) - Joselyn, Anita Shirley; Teddy, Dan Anna; Jose, Riya; Shanthini, Sharon; Joseph, Lallu; Rai, Ekta; Williams, Aparna
Abstract: Background: The time‐out protocol introduced by the Joint Commission is an important tool to prevent adverse events and improve safety in various health‐care environments. However, its implementation and utilization involve human, social, behavioral as well as system issues. Aims: The SMART aim of the current project was to increase the utilization of the time‐out protocol to more than 80% from baseline of 13%, over 6‐month period in all the magnetic resonance imaging (MRI) procedures performed at a tertiary care, teaching institute in South India. Methods: The Plan, Do, Study, Act (PDSA) cycle and root cause analysis strategies were utilized in this quality improvement initiative. The time‐out protocol was modified for MRI environment and put into practice to improve safety. Six months after the initiation of this safety protocol, our audit showed only a 13% compliance to the time‐out protocol. A multimodal strategy was utilized by involving all the stakeholders, educational interventions, and placing reminders for following the time‐out protocol, to affect change and achieve improvement in safety. Results: The compliance to time‐out protocol increased from 13% to 86% and the run chart showed that a special cause variation indicated by six points above the centerline at 86%. When analyzing individual components of the time‐out, the greatest improvement was noted in the ferromagnetic check of the personnel involved, namely, the Anesthesiologist, radiographer, and anesthesia technician. There were no delays in the list because of adherence to the time‐out protocol. Conclusion: Time‐out protocol in an MRI suite provides a final check to the anesthesia team before the anesthetized patient is wheeled into MR gantry. Using quality improvement methodology, we increased the compliance of time‐out protocol in the magnetic resonance imaging environment. Our study is an example how other institutions in India and elsewhere can adapt similar improvement strategies to enhance patient safety.